AB0948 Insufficient calcium intake in pediatric population with risk factors for osteoporosis. (15th June 2017) - Magallares, B Lόpez; Betancourt, J; Fraga, G; Pardo, N; Torrent, M; Marin, A; Herrera, S; Carreras, E; Casademont, J; Sierra, J Malouf
Abstract : Background: Compliance with daily calcium requirements in paediatric and young age is necessary to acquire peak bone mass, especially in populations that meet one or more risk factors for fractures Objectives: To study the characteristics of the pediatric population with at least one risk factor for developing low bone mass/osteoporosis and to measure their calcium intake Methods: Demographic and clinical data were prospectively collected from patients aged 2 to 20 years that met at least 1 risk factors for bone fragility, including: inflammatory diseases, treatment with Immunosuppressants and/or corticoesteroids, malabsortive disorders, chronic systemic disorders such as nephropathies or hematologic diseases, etc. The patients or their legal tutors signed the Informed Consent in order to participate in the study. The average daily calcium intake was collected through the Spanish INDICAD 2001 study survey, together with a comprehensive anamnesis. If patients or their family reported taking food not included in the survey, its calcium content were consulted in the Spanish Food Composition Database published by the BEDCA Network of the Ministry of Health Science and Innovation Results: Data were collected from 50 patients, with a mean age of 9.2 years (2–20), 28 (56%) female, 86% Caucasian, 6% Arab, 2% Asian and 6% Latin. The most frequent diagnoses were: Food intolerances/malabsorption: 32%, nephropathies: 22%, JIA: 16%, vasculitis: 10%, other inflammatory diseases: 8%. 42% had received systemic corticosteroids at some point, and 16% were receiving corticosteroids at present. Average daily calcium intake was 718 mg/d. They were divided by age groups, attending to daily calcium needs per group. In Table 1 we can observe the Recommended Daily Amount (RDA) of calcium by the Spanish Association of Pediatrics and the consumption collected, by age group. Only 3 children with low calcium intake were taking supplements.A decrease in calcium RDA adherence was observed with increasing age, statistically significant (p=0.009). There was also a lower calcium intake in the non-Caucasians compared to Caucasians statistically significant (p=0.044), which was not associated with age. Conclusions: Calcium intake in the population under 21 years old with at least 1 risk factor for developing low bone mass/osteoporosis is lower than recommended. In addition, recommendations are based on the physiological needs of the healthy population and it could be expected to be insufficient for those with chronic diseases. It should be noted that calcium intake in the groups with higher requirements (adolescents and young people) is lower, with a reduction in the proportion of patients who meet the compliance with the RDA as age increases. Studies with a larger population are needed to ratify these results together with serum calcidiol levels Disclosure of Interest: None declared